Предмет: Алгебра,
автор: karina3610
#4. 1)
#5. 1)
помогите пожалуйста
Приложения:
Ответы
Автор ответа:
0
2x²+2≤3x+9
2x²-3x+2-9≤0
2x²-3x-7=0
D=(-3)²-4*2*(-7)=9+56=65
x₁=(3-√65)/4≈1,27
x₂=(3+√65)/4≈2,77
- - +
--------------------(1,27)---------------------(2,77)------------------
x∈(-∞;2,77]
(x-2)(x+3)(x-1)²≥0
x-2=0 x+3=0 (x-1)²=0
x=2 x=-3 x-1=0
x=1
+ - - +
------------------(-3)-----------------------(1)-----------------(2)------------------
x∈(-∞;-3]∪[2;+∞)
2x²-3x+2-9≤0
2x²-3x-7=0
D=(-3)²-4*2*(-7)=9+56=65
x₁=(3-√65)/4≈1,27
x₂=(3+√65)/4≈2,77
- - +
--------------------(1,27)---------------------(2,77)------------------
x∈(-∞;2,77]
(x-2)(x+3)(x-1)²≥0
x-2=0 x+3=0 (x-1)²=0
x=2 x=-3 x-1=0
x=1
+ - - +
------------------(-3)-----------------------(1)-----------------(2)------------------
x∈(-∞;-3]∪[2;+∞)
Похожие вопросы
Предмет: Қазақ тiлi,
автор: mereitamdybek
Предмет: Алгебра,
автор: timurschew
Предмет: Литература,
автор: Аноним
Предмет: Математика,
автор: Sofa312
Предмет: История,
автор: pangella123